Lissencephaly– a rare cause of neonatal seizures - Dr. Pradnya P. Wali; Dr. Hemant Parakh; Dr. Krishna Reddy; Dr. Prashant Reddy (Pediatric Review: International Journal of Pediatric Research, 2018)
The most prominent feature of neurologic dysfunction in the neonatal period is seizures. The incidence of neonatal seizures is 0.5-3 per 1000 live births in term infants and 11-13% in premature babies. Although common causes of neonatal seizures comprises HIE, IVH, Sepsis, Hypoglycaemia, Hypocalcaemia etc. Sometimes rare causes like Neuronal migration syndrome can cause seizures in newborn. Lissencephaly is a smooth cerebrum with lack of convolutions of brain caused by defective neuronal migration during 12- 24 weeks of gestation. These Babies generally presents with seizures, developmental delay, difficulty in swallowing and short life span due to respiratory problems. Hereby we present a case of Lissencephaly as a cause of neonatal seizure disorder.